In vitro assessment of fracture resistance of endodontically treated teeth restored with short fiber reinforced resin based composite and ceramic overlays - Mona Elshirbini Hafez; Ahmed Ata Abd El-ghany; Ahmed Ismail Taha; Ashraf Amin (BMC Oral Health)
Abstract Background Conventional full-coverage crowns are used after endodontic treatment to enhance the fracture toughness of these teeth. However, these crowns lead to extensive loss of tooth structure. Continuous trials to develop a biomimetic conservative direct restorative material that can be used as a dentine substitute led to the development of the short fiber reinforced resin composite. Methods Fifty extracted intact upper premolar teeth were selected. Ten teeth serve as positive control without any treatment (Group 1). The remaining forty teeth were received root canal therapy. Standardized MOD cavities were prepared in 30 teeth of them, then they were randomly divided into three groups: Group 2: teeth received no coronal restorations; Group 3: MOD cavities restored with packable short fiber reinforced composite (EverX Posterior), followed by 2 mm nanocomposite; and Group 4: MOD cavities restored with flowable short fiber reinforced composite (EverX Flow), followed by 2 mm nanocomposite. For the remaining ten teeth, MOD cavities were prepared, and cusps were reduced to receive ceramic overlays (CeraSmart 270). After thermocycling, fracture load is applied using the Instron Universal machine until samples fracture. Fracture loads were recorded, and fracture mode was evaluated. All data were subjected to statistical analysis. Results Teeth restored with CeraSmart 270 overlays and those restored with high aspect ratio short fiber-reinforced resin composite recorded the highest resistance to fracture with no significant differences between them. Conclusions EverX Posterior may be considered a conservative substitute for indirect overlays to restore endodontically treated teeth with MOD cavities. Clinical relevance Clinically, using fiber reinforced composite as a substitute for indirect restorations preserves the tooth structure and provides proper resistance to fracture.